2021
DOI: 10.1016/j.ynstr.2021.100378
|View full text |Cite
|
Sign up to set email alerts
|

Neural connectome prospectively encodes the risk of post-traumatic stress disorder (PTSD) symptom during the COVID-19 pandemic

Abstract: Background The novel coronavirus (COVID-19) pandemic has affected humans worldwide and led to unprecedented stress and mortality. Detrimental effects of the pandemic on mental health, including risk of post-traumatic stress disorder (PTSD), have become an increasing concern. The identification of prospective neurobiological vulnerability markers for developing PTSD symptom during the pandemic is thus of high importance. Methods Before the COVID-19 outbreak (September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As shown in our previous publication, HBOT improved both depression and somatization symptoms in post-COVID-19 condition patients ( Zilberman-Itskovich et al, 2022 ). An association between COVID-19 related psychiatric symptoms and alternations in rsFC has been demonstrated in several studies ( Chen et al, 2021 , Fu et al, 2021 , Liu et al, 2021 , Sheynin et al, 2020 ). In the current study, we observed increased connectivity between the amygdala and left angular gyrus and the primary sensory-motor area, which are associated with the execution of cognitive emotion regulation initiated by frontal areas ( Kohn et al, 2014 , Kropf et al, 2018 ).…”
Section: Discussionmentioning
confidence: 80%
“…As shown in our previous publication, HBOT improved both depression and somatization symptoms in post-COVID-19 condition patients ( Zilberman-Itskovich et al, 2022 ). An association between COVID-19 related psychiatric symptoms and alternations in rsFC has been demonstrated in several studies ( Chen et al, 2021 , Fu et al, 2021 , Liu et al, 2021 , Sheynin et al, 2020 ). In the current study, we observed increased connectivity between the amygdala and left angular gyrus and the primary sensory-motor area, which are associated with the execution of cognitive emotion regulation initiated by frontal areas ( Kohn et al, 2014 , Kropf et al, 2018 ).…”
Section: Discussionmentioning
confidence: 80%
“…Comparing the PTSD prevalence rate before and after the pandemic, the obvious increase of this rate after the pandemic indicates a positive correlation between the pandemic and PTSD, and it is reasonable to assume that COVID-19 pandemic can be highly traumatic experiences. A recently study based on resting-state functional connectivity MRI (rs-fcMRI) also showed that COVID-19 pandemic was a crucial stressor to bring risks developing PTSD symptom [ 25 ]. The underlined result was consistent with the results of several recently published systematic review and meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Data for current study came from the project aligning with prior researches called the Behavior-Brain Research Project for Chinese personality traits (BBP) (Chen et al, 2021;Feng et al, 2021;He et al, 2021). Inclusion criteria for all participants were: history of chronic psychiatric (i.e., depression), current or history of medical (i.e., hypertension) or infectious diseases, taking prescription during the past 3 months, alcohol drinking or smoking per day, having an operation in the past one year, and in pregnancy (Table 1).…”
Section: Participantsmentioning
confidence: 99%